Billy Graham preaching at a rally in Wembley stadium (Module II, 2013)
London. Wembley Stadium. Footage of Billy Graham preaching at a rally asking members of the crowd to "surrender your will to Christ". Footage of crowds approaching Billy Graham at the rally.